Studi Fenomenologi Akuntabilitas Non Governmental Organization - Fikri, Ali; Sudarma, Made; Sukoharsono, Eko Ganis; Purnomosidhi, Bambang (Jurnal Akuntansi Multiparadigma, 2010)
The purpose of this study is to investigate the phenomenon of accountability in non-governmental organizations (NGOs). It seeks to understand accountability practices in NGOs and the conditions that sustain those processes and practices. NGOs have become important institutions in world affairs because many criticisms and problems associated with this sector. The research executes phenomenology as the methodology for the inquiry. Fieldwork was undertaken in WWF organization. The results indicate that public requires behavioral accountability, rather than reporting.